فقه الإمام إبراهيم النخعي وأثره في مذهب الحنفية في مسألة بيع مال ربوي بجنسه ومعهما أو مع أحدهما من غير جنسه: The Jurisprudence of Imām Ibrāhīm Al-Nakhaʿī and its Influence on the Ḥanafī School Regarding the Issue of Selling Ribā-Based Commodities for Their own Kind, Along with Something of A Different Kind, or With One of Them from A Different Kind - Bekim Karaliti (البصيرة: مجلة الدراسات الإسلامية, 2026)
This study aims to introduce the Tābiʿī and jurist of Kūfa, Imām Ibrāhīm al-Nakhaʿī, and to illustrate his jurisprudential views regarding an important topic in the field of sales: the sale of ribā-based commodities for their own kind, accompanied by something of a different kind, or alongside one of them from a different kind. The study examines this issue in detail, clarifies its various positions, and highlights al-Nakhaʿī’s influence on the Ḥanafī school in both its legal theory and applied rulings. It also investigates the methodology of Imām al-Nakhaʿī and its connection to the juristic method of the Ḥanafī madhhab. The research follows an inductive and analytical approach. The findings reveal the impact of al-Nakhaʿī’s jurisprudence on the Ḥanafī school, evident through the school’s agreement with him on this issue, their transmission of his opinion through their chains, and the multiplicity of narrations within the madhhab corresponding to the various narrations from al-Nakhaʿī, as well as their use of his statements as supporting evidence. The Ḥanafīs also concurred with al-Nakhaʿī in employing certain legal evidence, such as the Sunnah, qiyās (analogical reasoning), and the statements of the Companions.